The implementation of guided inquiry learning model to enhance students’ critical thinking skills on reaction rate topic: the case of an Indonesian public school - Efi Pujianti Puspita Dewi; Ratman Ratman; Kasmudin Mustapa (Universitas Negeri Malang, 2020)
The main objective of this research was to find out whether the implementation of guided inquiry learning model can improve students' critical thinking skills on the reaction rate topic at one public school located in Central Sulawesi, Indonesia. Experimental research method was used in this study pretest-posttest design. Two science program classes at the grade 11 were recruited. Both were assigned as experimental class 1 and experimental class 2. To measure students' critical thinking skills, the instruments used were critical thinking skills tests and observation sheets. Findings suggest that the critical thinking skills of students in the experimental class 1 was 44% which was in the very high category, 36% of them included in the high category, and 20% included in the medium category. In contrast, in the experimental class 2, students' critical thinking skills were 52% and included in the very high category, 24% of them included in the high category, and 24% included in the medium category. In addition, the N-gain test showcased that the average value for experimental class 1 was 0.75 (the high category) and experimental class 2 was 0.77 (the high category). Our findings concluded that the guided inquiry learning model can improve students' critical thinking skills on the reaction rate topic.